2015
DOI: 10.1177/1744629515586516
|View full text |Cite
|
Sign up to set email alerts
|

Social pedagogy as a model to provide support for siblings of children with intellectual disabilities

Abstract: The experiences of non-disabled children growing up with a sibling with an intellectual disability vary considerably, with reported impact ranging from increased mental health problems through evaluations of life enhancement. However, there is evidence that the net impact is neutral to positive, which was supported by the findings of this report of a service evaluation survey. The value of providing support to those young siblings is however clear. An established method of support is within a group of peers wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…These literacy narratives align with previous literacy research that show that parents within the dis/ability community need and search for ways to connect with others for both emotional and educational purposes (Carter et al, 2016; Gibbons & Gibbons, 2016; Gilson et al, 2018; Luijkx et al, 2016; Resch et al, 2012). To form these connections, parents reach out to those in similar situations to share texts and other literary resources.…”
Section: Discussionsupporting
confidence: 81%
“…These literacy narratives align with previous literacy research that show that parents within the dis/ability community need and search for ways to connect with others for both emotional and educational purposes (Carter et al, 2016; Gibbons & Gibbons, 2016; Gilson et al, 2018; Luijkx et al, 2016; Resch et al, 2012). To form these connections, parents reach out to those in similar situations to share texts and other literary resources.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is consistent with the study for the siblings of people diagnosed with a mental disorder that showed siblings mature faster and support their family [ 24 ]. Siblings played a significant role as emotional support and advocates [ 25 ] thus, siblings could facilitate adaptation and enhance the resilience of adolescents with disease [ 25 ]. The presence of siblings may be vital in helping to maintain a sense of security and emotional continuity, as well as self-identity [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…living in a neighborhood with a helpful atmosphere) can increase mothers' hope. On the contrary, for mothers of multiple children with and without intellectual disabilities, it might be necessary to provide them with the support for their children without disabilities, such as creating a peer group using social pedagogy (Carter et al, 2016).…”
Section: Discussionmentioning
confidence: 99%